2015
DOI: 10.1002/2015jd023326
|View full text |Cite
|
Sign up to set email alerts
|

Did the 2011 Nabro eruption affect the optical properties of ice clouds?

Abstract: The eruption of the Eritrean Nabro Volcano in June 2011 was the largest eruption since Mount Pinatubo in June 1991. The Nabro volcano emitted 1-1.5 megaton of sulfur dioxide into the lower stratosphere which resulted in a significant rise in the stratospheric sulfate aerosol burden in the months following the eruption. We have analyzed backscatter and extinction from ice clouds, as measured by the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observations (CALIPSO) satellite between June 2006 and May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
0
8
0
Order By: Relevance
“…Volcanic events during the instrumental period are, however, few and of limited magnitude, and their associated dynamical climatic response is very noisy (e.g., Hegerl et al, 2011). Furthermore, there is inter-model disagreement about post-eruption oceanic evolution, particularly concerning the response of the thermohaline circulation (e.g., Mignot et al, 2011;Hofer et al, 2011;Zanchettin et al, 2012;Ding et al, 2014). Substantial uncertainties still exist about decadalscale climate variability during periods of strong volcanic forcing and in the role of the ocean in determining the surface air temperature response to volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…Volcanic events during the instrumental period are, however, few and of limited magnitude, and their associated dynamical climatic response is very noisy (e.g., Hegerl et al, 2011). Furthermore, there is inter-model disagreement about post-eruption oceanic evolution, particularly concerning the response of the thermohaline circulation (e.g., Mignot et al, 2011;Hofer et al, 2011;Zanchettin et al, 2012;Ding et al, 2014). Substantial uncertainties still exist about decadalscale climate variability during periods of strong volcanic forcing and in the role of the ocean in determining the surface air temperature response to volcanic eruptions.…”
Section: Introductionmentioning
confidence: 99%
“…SO2 plume is tracked in this study using GOME-2 data sets as shown in the Figure 2. Stratospheric SO2 remained significantly high over Asia for a month after the eruption (Figure 2a; Meyer et al, 2015). Initially, the SO2 plume was mainly concentrated along East Africa until June 13, 2011 which later traveled a great distance to central Asia on June 15, 2011 (Figure 2b).…”
Section: Resultsmentioning
confidence: 94%
“…The eruption of Nabro Volcano generated a layer of sulfate aerosols, which resided in stratosphere for months (Sawamura et al, 2012). During the first 15 hours, a large fraction of total SO2 was released (Meyer et al, 2015). Monitoring Experiment-2 (GOME-2) is one of the new-generation European instruments carried on Met-Op.…”
Section: Mount Nabro Eruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meyer et al. (2015) investigated the impact on cirrus clouds from the Nabro eruption 2011 but found no significant impact on a global scale. Friberg et al.…”
Section: Introductionmentioning
confidence: 99%